2017
DOI: 10.1159/000470829
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Function and Endothelial Progenitor Cells in Patients with Severe Hypercholesterolemia and the Familial Hypercholesterolemia Phenotype

Abstract: Objective: To evaluate endothelial progenitor cells (EPCs) and systemic microvascular function in patients with severe hypercholesterolemia, comparing patients with the definite familial hypercholesterolemia (FH) phenotype (DFH) or probable/possible FH phenotype (PFH). There is a large spectrum of atherosclerotic disease between these two clinical phenotypes of FH, and to acquire further knowledge of the pathophysiology of vascular disease in both is desirable. Methods: Subjects with severe hypercholesterolemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The current trend in modeling of human diseases is to collect patient-specific iPSCs from individuals with hereditary pathologies and to elucidate the mechanisms of this pathology at the molecular and cellular levels using relevant cells obtained by iPSC differentiation [23]. Patientspecific iPSC-ECs are broadly used to model various disorders, including pulmonary arterial hypertension, Moyamoya disease, fibrodysplasia ossificans progressiva, Huntington's disease, Kawasaki's disease, type I diabetes mellitus, atrial or ventricular septal defects, pulmonary valve stenosis, cardiomyopathy, calcified aortic valve disease, hemophilia A, diabetic endotheliopathy, Hutchinson-Gilford Progeria Syndrome, cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy, and peripheral artery disease [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The current trend in modeling of human diseases is to collect patient-specific iPSCs from individuals with hereditary pathologies and to elucidate the mechanisms of this pathology at the molecular and cellular levels using relevant cells obtained by iPSC differentiation [23]. Patientspecific iPSC-ECs are broadly used to model various disorders, including pulmonary arterial hypertension, Moyamoya disease, fibrodysplasia ossificans progressiva, Huntington's disease, Kawasaki's disease, type I diabetes mellitus, atrial or ventricular septal defects, pulmonary valve stenosis, cardiomyopathy, calcified aortic valve disease, hemophilia A, diabetic endotheliopathy, Hutchinson-Gilford Progeria Syndrome, cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy, and peripheral artery disease [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…MVD is due to EC apoptosis and progressive loss of capillaries, which plays a major role in the development and progression of diabetic complications (diabetic retinopathy, nephropathy, and neuropathy). Patients with familial hypercholesterolemia also feature impaired endothelial-dependent vasodilatation [ 50 ].…”
Section: Etiology Of Padmentioning
confidence: 99%
“…Trial participants from both groups started with similar physical capacity at baseline according to their CPET results quantified by peak _ VO 2 (intervention group (mean [range]) 31.00 mL/min/kg vs. control group (mean [range]) 28.00 mL/min/kg; p ¼ 0.605, twotailed independent samples t-test) and anaerobic threshold (intervention group (mean [range]) 17.14 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] mL/min/kg vs. control group (mean [range]) 17.00 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] mL/min/kg; p ¼ 0.965, two-tailed independent samples t-test).…”
Section: Prehabilitation Increases Physical Capacity But Has No Effec...mentioning
confidence: 99%
“…In parts also referring to EPCs, a number of studies have shown the importance of exercise for microvascular health [ 12 , 13 , 14 , 15 , 16 , 17 ]. However, the mechanism of endothelial repair through EPCs and its role for microvascular health is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%